Development of the American Society of Colon & Rectal Surgeons (ASCRS) Rectal Cancer Surgery Checklist - Glasgow, Sean C. (Dis Colon Rectum, 2016)
BACKGROUND: There is excellent evidence that surgical safety checklists contribute to decreased morbidity and mortality. OBJECTIVE: To develop a surgical checklist comprising the key phases of care for rectal cancer patients. DESIGN: Consensus-oriented decision-making model involving iterative input from subject matter experts under the auspices of the American Society of Colon and Rectal Surgeons. RESULTS: The process generated a 25-item checklist covering the spectrum of care for rectal cancer patients undergoing surgery. LIMITATIONS: Lack of prospective validation. CONCLUSIONS: The American Society of Colon and Rectal Surgeons Rectal Cancer Surgery checklist comprises the essential elements of pre-, intra- and postoperative care that must be addressed during the surgical treatment of patients with rectal cancer.